Evaluation of brassicas for fall forage - Villalobos Villalobos, Luis Alonso (2013)
Various species and varieties of brassicas were evaluated for their potential to extend the grazing season and provide forage through late-fall and early winter in Colorado. The species and varieties evaluated included: rapes (Bonar, Winfred, and Barnopoli), turnips (Appin, Barkant, and Purple Top), kale (Kestral), turnip x rape hybrid (Pasja), swede (Major Plus), and radish (Groundhog). Each species/variety combination was established on two different planting dates (mid-July and mid-August) with four replicates. In order to assess the potential of the brassicas as a source of forage during the fall and early winter, the varieties were sampled at two different times (mid-October and mid-November) for their yield and nutritional value (crude protein, neutral detergent fiber, and in-vitro dry matter digestibility). The second planting date yielded less biomass compared to the first. Crude protein content of the brassicas was high for most varieties (16 to 28%); whereas the fiber content was lower compared to grasses (20 to 35%); and as a result of this, the digestibility was also high (80 to 94%). Delaying the establishment date can constrain the dry matter yield of brassicas which reduces their potential to supply forage during the fall and early winter. The information obtained from this project has enabled us to pick four brassica varieties (Barnopoli rape, Pasja hybrid, Barkant turnip, and Groundhog radish) with potential to be included in forage systems with cool-season grasses and legumes.